1993
DOI: 10.1038/365343a0
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and function of a quaternary signal transduction complex monitored by surface plasmon resonance

Abstract: We have used surface plasmon resonance biosensor technology to monitor the assembly and dynamics of a signal transduction complex which controls chemotaxis in Escherichia coli. A quaternary complex formed which consisted of the response regulator CheY, the histidine protein kinase CheA, a coupling protein CheW and a membrane-bound chemoreceptor Tar. Using various experimental conditions and mutant proteins, we have shown that the complex dissociates under conditions that favour phosphorylation of CheY. Direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
192
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(195 citation statements)
references
References 24 publications
2
192
0
1
Order By: Relevance
“…In vitro protein-protein interaction experiments indicate that CheW and CheA from E. coli are capable of forming a thermodynamically stable complex with chemoreceptors under physiological conditions (11,35). If R. centenum CheWCheAY forms a stable complex with receptors, communication with the polar flagellar motor would require that receptors be located near flagella.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro protein-protein interaction experiments indicate that CheW and CheA from E. coli are capable of forming a thermodynamically stable complex with chemoreceptors under physiological conditions (11,35). If R. centenum CheWCheAY forms a stable complex with receptors, communication with the polar flagellar motor would require that receptors be located near flagella.…”
Section: Discussionmentioning
confidence: 99%
“…The construct was transformed in E. coli BL21 (DE3)/pLysS for inducible expression by isopropyl thiogalactopyranoside (IPTG; final concentration, 1.5 mM). Selective labeling of protein(s) expressed from the T7 promoter with 35 S was achieved by treating cells with rifampin prior to addition of [ 35 S]methionine as described previously (41,42). The CheAY polypeptide was visualized by denaturing sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis (PAGE) and standard autoradiography (33).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the affinity-purified cyclin G, after removal of the GST portion by treatment with thrombin, displayed a single band at the expected size on SDS-PAGE (data not shown). Analysis by surface plasmon resonance biosensor technology [11,[27][28][29] suggested that GAK directly associates with GST-cyclin G, probably via the kinase domain at the Nterminus of the molecule. In this experiment, anti-GST antibody was covalently attached to the dextran matrix of a BIAcore sensor chip to assess the association at a neutral pH value.…”
Section: Analysis Of the Cyclin G-gak Interaction Using Thementioning
confidence: 99%
“…This possibility is consistent with results from 1 H-and 15 N-NMR spectroscopy on CheY D13K, which allow for a small percent of the D13K mutant molecule to be in an alternate conformation, rapidly interconverting with its resting state. 2 Comparison of Wild-type and CheY D13K Activities-CheY binds specifically to three different proteins: CheA, which donates the phosphoryl group to CheY (43)(44)(45)(46); CheZ, which stimulates dephosphorylation of CheY-P (43,(47)(48)(49); and FliM, the recipient of the activating signal of CheY, located in the flagellar switch complex (34,50). Phosphorylation of wild-type CheY reduces binding to CheA but enhances binding to CheZ and FliM.…”
Section: å X-ray Structure Of Chey Mutant D13kmentioning
confidence: 99%